2012
DOI: 10.1111/j.1538-7836.2012.04817.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and prevention of catheter‐related thrombosis in patients with cancer

Abstract: Summary.  Central venous catheters are extensively used in patients with cancer to secure delivery of chemotherapy and facilitate phlebotomy. Unfortunately, considerable morbidity can result from early complications or late sequelae, ranging from arterial puncture, pneumothorax and bloodstream infections to catheter‐related thrombosis (CRT). Contemporary studies have shown that the incidence of symptomatic CRT is ∼ 5%, whereas the incidence of asymptomatic CRT is higher, at 14–18%. The significance and mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
17

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 73 publications
3
51
0
17
Order By: Relevance
“…Symptomatic catheter-related deep vein thrombosis is reported in about 5% of oncologic patients [26]. Referring to patient-based data, these results are comparable to our own study results (1.0%).…”
Section: Discussionsupporting
confidence: 82%
“…Symptomatic catheter-related deep vein thrombosis is reported in about 5% of oncologic patients [26]. Referring to patient-based data, these results are comparable to our own study results (1.0%).…”
Section: Discussionsupporting
confidence: 82%
“…4 Symptomatic thrombosis occurs in at least 5% of cancer patients with CVCs and is a serious problem because it often delays cancer treatment, prolongs hospital stay, and increases health care costs by necessitating anticoagulant therapy in patients at risk for bleeding. 4 The pathogenesis of thrombosis in patients with CVCs is unclear. Low doses of warfarin and prophylactic low-molecular-weight heparin do not reduce the risk of CVC-associated thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in contrast to existing evidence [17], we found that in-hospital administration of pharmacological VTE-prophylaxis trended towards preventing PICC-DVT. As the majority of available data regarding catheter-DVT comes from patients with cancer [26][27][28] who often receive non-PICC devices [29,30], our findings regarding antiplatelet agents and effects of VTE prophylaxis may relate to important differences in study population and device characteristics. Given the existence of other supportive data regarding the influence of VTE prophylaxis on PICC-DVT [31][32][33] and a potentially protective role of statins on thrombosis [34], further, controlled studies of VTE prophylaxis, antiplatelet treatment and statins to prevent PICC-DVT appear warranted.…”
Section: Discussionmentioning
confidence: 89%